Nyilvános diplomácia Közép-Kelet Európában - Nagy, Lilla (Közép-Európai Közlemények, 2012)
Public diplomacy is the ways to communicate and engage with foreign publics in order to create a favorable country image, mutual understanding and to promote foreign policy goals. Public diplomacy is an important aspect of the foreign policy of post soviet eastern-European nations in order to rebrand themselves and truly integrate into the European community. This may not be easy, but nations in the region have created different techniques to cope with invisibility, stereotypes, negative image and to demonstrate being European. Among these nations Hungary has also made the firsts steps to work on its image. Elements of public diplomacy do exist and we have seen successful public diplomacy initiatives as well. Nevertheless there is still a lot to be learnt in the post Soviet region to develop comprehensive public diplomacy strategies. In this paper I will try to summarize the efforts and results of Central-Easter European public diplomacy.